2022
DOI: 10.1111/1467-9566.13435
|View full text |Cite
|
Sign up to set email alerts
|

‘I'll put up with things for a long time before I need to call anybody’: Face work, the Total Institution and the perpetuation of care inequalities

Abstract: Failures in fundamental care (e.g. nutrition or pain‐relief) for hospitalised patients can have serious consequences, including avoidable deaths. Policy rhetoric of ‘shared decision‐making’ fails to consider how structural constraints and power dynamics limit patient agency in nursing staff‐patient interactions. Goffman's concepts of face work, the presentation of self and the Total Institution shaped our analysis of interview and focus group data from hospital patients. Patients avoided threatening ‘good’ pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Across both the quantitative and qualitative data, the gap in knowledge regarding cannabis and the need for continuing education for HCPs working in LTC were readily apparent. When HCPs are unfamiliar about the various forms of medical cannabis, appropriate dosing and titration schedules, and routes of administration, they are hindered in their ability to engage in shared decision making with LTC residents as well as provide high-quality care [ 51 54 ]. Education is particularly needed that is tailored to the unique risks and benefits of medical cannabis use among LTC populations, including those living with physical and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Across both the quantitative and qualitative data, the gap in knowledge regarding cannabis and the need for continuing education for HCPs working in LTC were readily apparent. When HCPs are unfamiliar about the various forms of medical cannabis, appropriate dosing and titration schedules, and routes of administration, they are hindered in their ability to engage in shared decision making with LTC residents as well as provide high-quality care [ 51 54 ]. Education is particularly needed that is tailored to the unique risks and benefits of medical cannabis use among LTC populations, including those living with physical and cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…These patients were often looking for someone to support them emotionally as well as physically through their experience. Medical care is often prioritised over emotional support when patient need outstrips resources ( Hope et al, 2022 ). Time pressures, lack of resources and a focus on task-based work practices all conspire against establishing rich communicative relationships in today’s healthcare practice ( Kidd & Carel, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wider workforce and external challenges, such as excessive workloads and inadequate staffing, can have a significant impact on leadership styles. For patients, their families and/or carers, witnessing these pressures can deter them from raising worries due to fears of being a ‘burden’ or ‘imposing on already busy staff 4,11–13 . Despite national policies and procedures directly aimed at speaking up about concerns, 14 the outcome of the trial of Lucy Letby in the United Kingdom demonstrated patients’ families and staff did not feel safe to raise concerns or confident that they would be followed by a prompt response 15…”
mentioning
confidence: 99%
“…For patients, their families and/or carers, witnessing these pressures can deter them from raising worries due to fears of being a 'burden' or 'imposing on already busy staff. 4,[11][12][13] Despite national policies and procedures directly aimed at speaking up about concerns, 14 the outcome of the trial of Lucy Letby in the United Kingdom demonstrated patients' families and staff did not feel safe to raise concerns or confident that they would be followed by a prompt response. 15 Evidence suggests collaborative leadership, compared to commandand-control, can facilitate better communication and collaboration among stakeholders, increase staff confidence in responding to care concerns, and allow patients to take a more active role in their care.…”
mentioning
confidence: 99%